In vitro functional characterization of androgen receptor gene mutations at arginine p.856 of the ligand-binding-domain associated with androgen insensitivity syndrome. Issue 208 (April 2021) - Tajouri, Asma; Kharrat, Maher; Trabelsi, Mediha; M'rad, Ridha; Hiort, Olaf; Werner, Ralf
Highlights: A female patient with a classic picture of complete androgen insensitivity syndrome. A novel mutation in the AR gene was identified by direct sequencing: p.R856L. Functional studies were performed to investigate the functional properties of p.R856L. p.R856L mutation strongly affected both transactivation capacity and N/C interaction. Functional studies confirmed the pathogenicity of p.R856L mutation. Abstract: Androgens are critical for male sex differentiation. Their actions are mediated by the androgen receptor (AR). Mutations disrupting AR function result in the androgen insensitivity syndrome (AIS). In this study, we identified in a patient with complete AIS, a novel AR mutation p.R856L. To investigate the functional properties of p.R856L, we performed functional studies. In comparison, we have characterized two already described mutations: p.R856H and p.R856C. We used a model composed of two different promoters fused to a reporter gene, two cell lines, and showed that all mutations were able to transactivate the (ARE)2 -TATA promoter expressed in CHO cells more highly. Moreover, we confirmed the pathogenicity of the p.R856L and p.R856C mutations, and their associations with complete AIS. In contrast, the p.R856H mutation, which is associated with a spectrum of AIS phenotypes, showed less severe transcriptional constraints. Altogether, our studies allowed us to better characterize arginine residue at p.R856 position.